Impact of Pre-operative Aerobic Exercise on Cardiometabolic Health and Quality of Life in Patients Undergoing Bariatric Surgery - Gilbertson, Nicole M.; Eichner, Natalie Z. M.; Khurshid, Mahnoor; Rexrode, Elizabeth A.; Kranz, Sibylle; Weltman, Arthur; Hallowell, Peter T.; Malin, Steven K. (Frontiers in Physiology, 2020)
Objective. Examine the effect of aerobic exercise (EX) combined with standard medical care (SC) (EX+SC) compared to SC alone on cardiometabolic health and quality of life in relation to surgical outcomes. Methods. Patients receiving bariatric surgery were match-paired to 30 d of pre-operative SC (n=7, 1 male, 39.05.3 y, body mass index 46.4±3.0 kg/m2; low calorie diet) or EX+SC (n = 7, 0 males, 45.64.8 y, body mass index 43.9±4.2 kg/m2; walking 30min/d, 5d/wk, 65-85% HRpeak). Body mass, waist circumference, cardiorespiratory fitness (VO2peak), high sensitivity C-reactive protein (hs-CRP), cytokeratin 18 (CK18), weight related quality of life (QoL), and a 120 min mixed meal tolerance test (MMTT) was performed to assess arterial stiffness via augmentation index normalized to a heart rate of 75 beats per minute (AIx@75), whole-body insulin sensitivity, and glucose total area under the curve (tAUC) pre- and post-intervention ( 2 d prior to surgery). Length of hospital stay (admission to discharge) was recorded. Results. EX+SC had a greater effect for decreased intake of total calories (P=0.14; ES=0.86) compared to SC, but no change in body weight or waist circumference was observed in either group. EX+SC had a greater effect for increased VO2peak (P=0.24; ES=0.91) and decreased hs-CRP (P=0.31; ES=0.69) compared to SC. EX+SC reduced circulating CK18 (P=0.05; ES=3.05) and improved QoL (P=0.02) compared to SC. Although EX+SC had no statistical effect on arterial stiffness compared to SC, we observed a modest effect size for AIx@75 tAUC (P=0.36; ES=0.52). EX+SC had a significantly shorter length of hospital stay (P=0.05; ES=1.38) than SC, and a shorter length of hospital stay was associated with decreased sugar intake (r=0.55, P=0.04). Decreased AIx@75 tAUC significantly correlated with improved whole-body insulin sensitivity (r=-0.59, P=0.03) and glucose tAUC (r=0.57, P=0.04). Conclusion. EX with SC for 30 days prior to bariatric surgery may be important for cardiometabolic health, quality of life, and surgical outcomes in the bariatric patient.